Effects of video micro teaching plan to improve archery technique in university students - Yang, A.; Wattanapayungkul, Y. (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: Video microteaching not only improves student learning outcomes but also optimizes the teaching process for instructors. By making effective use of video resources, teachers can dedicate more class time to individual tutoring, helping students who need more attention to overcome learning challenges. Therefore, the objectives of this research were: (1) to study the effect of a video microteaching program on the improvement of archery skills at Jilin University, and (2) to compare the effect of video a microteaching plan on improving archery technique at Jilin University.